A mini-review of MXene porous films: Preparation, mechanism and application. (20th March 2022) - Zhang, Yali; Yan, Yi; Qiu, Hua; Ma, Zhonglei; Ruan, Kunpeng; Gu, Junwei
Abstract: MXene presents excellent electrical conductivity, abundant surface functional groups and wonderful film-forming performance, but the lamellar layers are prone to self-stacking during film formation, which will reduce the loss of electromagnetic waves, hinder ion transmission, and limit the effective load of other functional materials. The construction of the porous structure can effectively solve the self-stacking problem of MXene sheets. This article reviews the research progress of MXene porous films for electromagnetic interference (EMI) shielding, lithium/sodium ion batteries, pseudocapacitors, and biomedical science applications. It focuses on the preparation methods of MXene porous films, and discusses the pore-forming mechanism of the porous structure formed by different preparation methods and the internal relationship between the "microstructure-macroscopic performance" of the MXene porous films, points out the key scientific and technical bottlenecks that need to be solved urgently in the preparation and application of the MXene porous films. It is hoped to provide certain guidance for the design, preparation, optimization, industrial application, and development of MXene porous films. Highlights: The progress of MXene porous films for various applications is reviewed. Preparation methods of MXene porous films and pore-forming mechanisms are discussed. "Microstructure-macroscopic performance" relationship of MXene porous films is illustrated. Key bottlenecks of MXene porous films are pointed out and future solutions are raised.